Search for disappearing tracks in proton-proton collisions at root s=8 TeV - KAYA, MİTHAT (My University, 2015)
A search is presented for long-lived charged particles that decay within the CMS detector and produce the signature of a disappearing track. Disappearing tracks are identified as those with little or no associated calorimeter energy deposits and with missing hits in the outer layers of the tracker. The search uses proton-proton collision data recorded at root s = 8 TeV that corresponds to an integrated luminosity of 19.5 fb(-1). The results of the search are interpreted in the context of the anomaly-mediated supersymmetry breaking (AMSB) model. The number of observed events is in agreement with the background expectation, and limits are set on the cross section of direct electroweak chargino production in terms of the chargino mass and mean proper lifetime. At 95% confidence level, AMSB models with a chargino mass less than 260 GeV, corresponding to a mean proper lifetime of 0.2 ns, are excluded.
Keywords: Fizik; Temel Parçacıklar ve Alanlar; Temel Bilimler; Physics; Basic Particles and Areas; Natural Sciences; FİZİK, PARÇACIKLAR VE ALANLAR; Temel Bilimler (SCI); PHYSICS, PARTICLES & FIELDS; PHYSICS; Natural Sciences (SCI); Hadron-Hadron Scattering; Supersymmetry; Exotics; Hadron-Hadron Scattering; Supersymmetry; Exotics